2005
DOI: 10.1111/j.0105-1873.2005.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Selected oxidized fragrance terpenes are common contact allergens

Abstract: Terpenes are widely used fragrance compounds in fine fragrances, but also in domestic and occupational products. Terpenes oxidize easily due to autoxidation on air exposure. Previous studies have shown that limonene, linalool and caryophyllene are not allergenic themselves but readily form allergenic products on air-exposure. This study aimed to determine the frequency and characteristics of allergic reactions to selected oxidized fragrance terpenes other than limonene. In total 1511 consecutive dermatitis pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
172
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(185 citation statements)
references
References 47 publications
11
172
0
1
Order By: Relevance
“…While linalool itself may have limited allergenic properties, it can auto-oxidize upon air exposure into a hyperoxide species [21] which can lead to contact allergy responses in mice [22]. In a study of 1511 dermatitis patients, auto-oxidized linalool was shown to induce allergenic responses in 1.3 % of those tested, with 1.1 % of patients sensitive to the linalool hyperoxide fraction, using patch tests [23]. A follow-up study, again involving 1511 dermatitis patients, showed that exposure to oxidized linalool at concentrations of > 6.0 % resulted in allergenic irritation in 5-7% of test subjects [24].…”
Section: Studies In Human Subjectsmentioning
confidence: 99%
“…While linalool itself may have limited allergenic properties, it can auto-oxidize upon air exposure into a hyperoxide species [21] which can lead to contact allergy responses in mice [22]. In a study of 1511 dermatitis patients, auto-oxidized linalool was shown to induce allergenic responses in 1.3 % of those tested, with 1.1 % of patients sensitive to the linalool hyperoxide fraction, using patch tests [23]. A follow-up study, again involving 1511 dermatitis patients, showed that exposure to oxidized linalool at concentrations of > 6.0 % resulted in allergenic irritation in 5-7% of test subjects [24].…”
Section: Studies In Human Subjectsmentioning
confidence: 99%
“…9,10) In experimental dermopharmacy terpenes are widely used as penetration enhancers. 11) The structure of investigated terpenes is presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Kwon-Ghung and Bennette, [24] studied the pathogenic aspects of Aspergillus, responsible for most human systemic infections. Matura et al [25] investigated the role of some terpens play as causative agents of contact dermatitis and fragrance allergies. Our results indicate that, there is decrease in terpenoid pool with ageing of the bark.…”
Section: Resultsmentioning
confidence: 99%